Drought and el nino phases in Zimbabwe - Shoko, Kampion; Shoko, Nothabo (Midlands State University, 2015)
The desk study was carried out to assess the frequency of drought associated with the various phases of the El Nino. Southern Oscillation index (SOI) values were analysed to determine El Nino or La Nina years. Three meteorological definitions of drought were used to establish one which correlates best with the El Nino or La Nina years. Annual mean rainfall data from the meteorological department ranging from 1901 to 1997 saved as the data base for the study. The corresponding annual mean SOI values for the same period were obtained from the Australian Weather Bureau website. For a particular year, the annual mean rainfall was correlated to the previous and current monthly mean SOI values. Analysis of the SOI values revealed that the probability of El Nino occurrence is 47 % and that of La Nina is 49 %. Results from the definitions of drought revealed that the probability of the occurrence of El Nino induced drought was 34% and the probability of the occurrence of La Nina induced wet years was 30 % . The study recommends that more detailed research be carried out on the association of ENSO phases and Zimbabwe’s rainfall pattern to improve the precision of the current seasonal rainfall forecasting model.